Law and Gospel : Philip Melanchthon's debate with John Agricola of Eisleben over poenitentia - Wengert, Timothy J. (Texts and studies in Reformation and Post-Reformation thought, 1997)
1.Calm before the Storm: Agricola's Biblical Exegesis from 1525 to 1527 --2.Flood of Catechisms (1525-27) --3.Melanchthon's First Attacks on Agricola (1527) --4.Tempest in the Torgau (August-November 1527) --5.Aftermath (1527-53) --6.Justifying Good Work: The Origins of the Concept of the Third Use of the Law (1534) --App. 1.Exegetical Works of John Agricola --App. 2.Early Catechisms (Additions to the Work of Ferdinand Cohrs) --App. 3.Printing History of the Latin Version of Philip Melanchthon's Visitation Articles.